Molecular taxonomic reassessment and phylogenetic relationships of Middle Eastern Cyprinidae inferred from mitochondrial COX1 sequences retrieved from GenBank - Bannai, Majid (Iraqi Journal of Aquaculture, 2026)
Cyprinidae is the most diverse and taxonomically challenging group of freshwater fish in the Middle East, where species identification is difficult due to morphological similarity and taxonomic instability. This paper presents a molecular taxonomic review and phylogenetic analysis of Middle Eastern cyprinids based on mitochondrial COX1 gene sequences downloaded from GenBank. A large dataset of publicly available COX1 sequences from various cyprinid genera and locations across the Middle East was assembled and analyzed. Alignment and genetic distances were calculated, and phylogenetic relationships were analyzed using Neighbor-Joining (NJ) and Minimum Evolution with bootstrap validation. The resulting phylogenetic trees revealed well-defined clades corresponding to recognized taxonomic groups, but also uncertainty in species delimitation and unpredictable clustering among closely related taxa. Although based on a single mitochondrial marker, the data demonstrate COX1's utility in resolving species-level relationships and provide initial insights into shallow phylogeographical structuring among Middle Eastern cyprinids. These patterns suggest potential taxonomic confusion and highlight the importance of integrative analyses incorporating other markers and morphological data. This study provides a molecular framework for elucidating cyprinid systematics in the Middle East and serves as a foundation for future evolutionary and systematic research.